Employee Performance Assessed from Turnover, Work Conflict, and the Working Environment - Nita Silviana (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2021)
Turnover refers more to the maintenance level of tbsp. Work conflicts lead to the level of problems that occur within the scope of the company. The work environment describes the work atmosphere and the availability of facilities and infrastructure that can directly affect employee performance. The purpose of this study is to prove the results of employee performance in terms of turnover, work conflict, and the work environment of PT. Kinarya Tunas Artha. Using descriptive and quantitative research types. Total population 200 respondents, sample 67 respondents, using multiple linear regression analysis. Research results: f test describes turnover, work conflict & work environment affect employee performance. While the t-test states that turnover has a positive & significant effect, work conflict has a negative and significant effect, the work environment has a positive and significant effect on employee performance. The results obtained R2/ coefficient of determination of the effect of turnover, work conflict, and work environment on the performance of 53.5%, the work environment variable becomes dominant because the tcount is the largest.